1976
DOI: 10.1007/bf01318008
|View full text |Cite
|
Sign up to set email alerts
|

Simian virus 40-Chinese hamster kidney cell interaction II. The semipermissivity of the cell system

Abstract: Throughout in vitro passages, Chinese hamster kidney (CHK) cells progressively lost susceptibility to SV 40 virus infection while remaining continuously susceptible to viral DNA infection. Upon infection with SV 40 virus or viral DNA, the CHK cell line supported viral DNA and virus replication at a low level. SV 40 transformed CHK cell lines spontaneously produced small amounts of viral DNA and virions. The percentage of virus-producing cells was low. Various clones derived from each of these lines behaved as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1976
1976
1985
1985

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…We have further shown that Chinese hamster kidney cells, whether transformed or not by SV40, were all potentially permissive for the virus (12,13).…”
Section: Introduetionmentioning
confidence: 97%
“…We have further shown that Chinese hamster kidney cells, whether transformed or not by SV40, were all potentially permissive for the virus (12,13).…”
Section: Introduetionmentioning
confidence: 97%
“…Upon infection with SV4o virus or virus DNA, Chinese hamster kidney cells supported virus DNA and virus synthesis at a low level and this cell system was defined as semipermissive (Lavialle et al 1976). To demonstrate infectious SV4o virus synthesis, these cells had to be infected with virus DNA in order to overcome their limited susceptibility to the virus particles and to avoid masking of the virus progeny by the input virus inoculum (Lavialle et aL I976).…”
Section: Stimulation Of S V4o Production By MC Treatment Of Chk Cl Imentioning
confidence: 99%
“…There was no significant difference between these clones, at least in terms of the total number of Chinese hamster chromosomes identified. These three superhybrid clones were also capable of synthesizing SV40 V-antigen and virus after superinfection [15], Knowing that the Chinese hamster kidney cells, whether transformed or not by SV40, were all potential ly permissive for the virus [11] we thought it was im portant to try and see whether or not certain chromo somal pairs were involved in the expression of viral functions. Therefore, we compared each pair of Chinese hamster chromosomes present in Cl 6d with its evolu tion in Cl 6d.6BU.…”
Section: Comparison Of Mouse Chromosomes (Fig 5 Table Vi)mentioning
confidence: 99%